FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI DI DESA RAMUNIA I KECAMATAN PANTAI LABU KABUPATEN DELI SERDANG - Sukma Ayu Prawati; Meutia Nanda; Windah Angraini Harahap; Tamara Aini Imanta (Jurnal Keperawatan dan Kesehatan Masyarakat Cendekia Utama, 2023)
Hypertension is a condition in which blood pressure increases drastically. This is the health problem with the highest prevalence in Indonesia (Riskesdas 2018). The purpose of this study was to determine the factors associated with the incidence of hypertension in  kelurahan Pantai Labu , Desa Ramunia I ,Kabupaten Deli Serdang in 2022. This study was a quantitative study, with a cross sectional approach. The total population is 450 people consisting of Dusun I, II and III, and the number of samples is 80 respondents. The research instrument by distributing questionnaires to the public was then tested with a chis-quare statistical test. The results of this study obtained (57.8%) of respondents aged 44-53 years, (69%) of respondents had a bad diet, (53.6%) of respondents experienced normal stress and (56.8%) of respondents consumed cigarettes. Hypertension can occur due to lack of physical activity, education, poor diet, and smoking habits. From the statistical test results, it was found that there was a relationship between the age factor and the incidence of hypertension with a p-value of 0.000, there was a relationship between dietary factors and the incidence of hypertension with a p-value of 0.000, there was a relationship between stress factors and the incidence of hypertension with a p-value of 0.000. smoking on the incidence of hypertension with a p-value of 0.000, from these variables it can be concluded that these factors are related to the incidence of hypertension in the community in the area of Desa Ramunia I, Kecamatan Pantai Labu, Kabupaten Deli Serdang. Suggestions from this study are that people are expected not to smoke and reduce foods that contain high iodine and be able to cope with stress by carrying out activities such as sports and making discussions or places of business for the community in  Desa Ramunia I, Kecamatan Pantai Labu,  Kabupaten Deli Serdang.